Characterization of Tool Clamping Conditions in Forging Hammers - Nico Wagner; Robert Tehel; Robin Kurth; Steffen Ihlenfeldt (Journal of Machine Engineering)
The present work addresses the topic of die clamping at the forging hammer in the context of the definition of a current requirement profile as well as the evaluation of individual influencing variables on the clamping process. In addition to the presentation of survey results for the requirements profile, the first part focus on the sensible minimization of influencing variables to be investigated and on the verification of a possible evaluation meth-od. Based on this, in the second part, exemplary influencing variables on the clamping condition are investigat-ed by means of FEM, whereby it can be shown, as an example, that the forging process heat flow is without sig-nificant influence on the clamping state of the dies.